STRENGTHENING LOCAL GOVERNMENT'S ROLE IN IMPLEMENTING SUSTAINABLE BUDGETING THROUGH ENVIRONMENT-BASED BUDGETING IN INDONESIA - Taufik Kurrohman; Siska Aprilia Oktaviani (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
Environmental-based budgeting is one of the strategies to achieve the Sustainable Development Goals (SDGs), which were launched globally, including in Indonesia. This study examines whether value-for-money-based local government budgeting can be elaborated to incorporate environmental aspects and their implications for financial reporting. Its objective is to analyze the possibility of implementing sustainable budgeting through economic valuation in the Regional Budget (APBD). Its novelty lies in the implementation of economic valuation in government budgeting and its implications for financial reporting, which are highly relevant today. The research method is a mixed quantitative and qualitative approach, with economic valuation and qualitative analysis through case studies and policy documents. The results indicate that sustainable budgeting can be implemented with specific technical guidelines such as environmental indicators, green budget tagging, and a participatory approach. By implementing this budgeting, local governments will contribute positively to economic growth without harming the environment.